2005
DOI: 10.1677/erc.1.01045
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–drug conjugates: towards a novel approach for the treatment of endrocine-related cancer

Abstract: The last decade has seen successful clinical application of polymer-protein conjugates (e.g. Oncaspar, Neulasta) and promising results in clinical trials with polymer-anticancer drug conjugates. This, together with the realisation that nanomedicines may play an important future role in cancer diagnosis and treatment, has increased interest in this emerging field. More than 10 anticancer conjugates have now entered clinical development. Phase I/II clinical trials involving N-(2-hydroxypropyl)methacrylamide (HPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(89 citation statements)
references
References 55 publications
1
84
0
4
Order By: Relevance
“…Many such carrier-bound agents have entered clinical trials with promising results, which has opened a wide field for further challenging exploration. The topic has been amply reviewed over the past two decades [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Polymer-drug Conjugation: a Background Discussionmentioning
confidence: 99%
“…Many such carrier-bound agents have entered clinical trials with promising results, which has opened a wide field for further challenging exploration. The topic has been amply reviewed over the past two decades [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Polymer-drug Conjugation: a Background Discussionmentioning
confidence: 99%
“…Although the optimum size of the polymer-drug nanoconjugate required for effective accumulation in the tumour by EPR effect is not yet known, direct observation of the tumor vasculature has demonstrated a tumor-dependent cut off size of 200 nm -2 μm (102,103) while nanoparticle-dependent studies indicated cut off size of 200 nm -1.2 μm (104). In the same vein polymer nanoconjugates with molecular diameter 5 -20 nm has been reported to exhibit excellent intratumoural penetration (uptake) comparable to liposomes and nanoparticles (105). It is well documented that polymer-drug nanoconjugates can increase the therapeutic index of anticancer agents through enhanced permeability and retention (EPR) effect (99,100,(106)(107)(108)(109).…”
Section: Passive Targetingmentioning
confidence: 96%
“…This increased access to diverse STIs will certainly expand our capacity for rational mono-and combined therapies in cancer. It was also encouraging to hear from Duncan that state-of-the-art drug delivery may allow more efficient and specific therapeutic targeting of the cancer cell, potentially allowing the complex therapeutic targeting strategies proposed in this Workshop to become a reality (Duncan et al 2005).…”
Section: Summary and Challenges For The Future Use Of Stis In Breast mentioning
confidence: 96%